2021
DOI: 10.21203/rs.3.rs-154011/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exosome-associated Mitochondrial DNA is Elevated in Patients with ME/CFS and Stimulates Human Cultured Microglia to Secrete IL-1β

Abstract: Background: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS) is a debilitating disease that presents with fatigue, sleep disturbances, malaise and cognitive problems. The pathogenesis of ME/CFS is presently unknown and serum levels of potential biomarkers have been inconsistent. Methods: Exosomes were purified from serum obtained from patients with ME/CFS before and after exercise and their content of mitochondrial DNA (mtDNA) was determined by quantitative PCR. Exosomes from both patients and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 60 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…The second study assessed circulating mitochondrial DNA (mtDNA) levels associated with exosomes in response to physical exercise. The exosomes from patients with and without ME/CFS were incubated with a human microglial cells and release of IL-1β was measured ( Theoharides et al, 2021 ). The analysis showed that after exercise exosome-associated mtDNA was increased in patients with ME/CFS but not controls and that in cell culture there was significantly increased secretion of IL-1β from microglial cells.…”
Section: The Case For Neuroglial Dysfunction In Myalgic Encephalomyel...mentioning
confidence: 99%
“…The second study assessed circulating mitochondrial DNA (mtDNA) levels associated with exosomes in response to physical exercise. The exosomes from patients with and without ME/CFS were incubated with a human microglial cells and release of IL-1β was measured ( Theoharides et al, 2021 ). The analysis showed that after exercise exosome-associated mtDNA was increased in patients with ME/CFS but not controls and that in cell culture there was significantly increased secretion of IL-1β from microglial cells.…”
Section: The Case For Neuroglial Dysfunction In Myalgic Encephalomyel...mentioning
confidence: 99%